Modelación y control de un sistema hibrido fotovoltaico eólico conectado a la red (2022)
The present research work studies the modeling and simulation of a hybrid system made up of photovoltaic panels and wind turbines proposed for study in an area of reference which was selected the municipality of Riohacha, La Guajira. The work is comprised first of all in carrying out the sizing and selection of equipment that will make up the hybrid system taking into account the given conditions of the area, For this, the technical specifications of the equipment offered by different manufacturers are reviewed.